Performance of Broiler Chickens Fed Low Non Phytate Phosphorus Diets Supplemented with Microbial Phytase - Arun K. Panda; Savaram V. Rama Rao; Mantena V.L.N. Raju; Shyam S. Gajula; Shishir K. Bhanja (The Journal of Poultry Science, 2007)
An experiment was conducted with 270 broiler chicks to examine the effect of microbial phytase supplementation to low non-phytate phosphorus (NPP) diets on growth performance, bone mineralisation and nutrients retention during 1 to 21 days of age. Four isonitrogenous and isocaloric diets were formulated to contain 0.30, 0.35, 0.40 and 0.45% NPP with the two lowest NPP levels (0.30 and 0.35%) supplemented with microbial phytase (500FTU per kg diet). Each diet was offered ad libitum to 9 replicates of 5 chicks each throughout the experimental period. The performance in terms of body weight gain, feed intake and feed/gain was significantly depressed in chicks fed lowest level of NPP (0.30%). Supplementation of phytase to either 0.30 or 0.35% NPP diet significantly improved body weight gain and feed conversion, which was comparable with 0.40% NPP diet. The leg abnormality increased and, tibia ash and tibia breaking strength decreased significantly in diets containing 0.30 and 0.35% NPP. Increasing NPP level to 0.40% or supplementing 500FTU phytase/kg diet to 0.30 and 0.35% NPP diets alleviated leg abnormality and enhanced tibia breaking strength and ash content. Serum Ca concentration was not influenced, but serum concentration of P and protein increased significantly either by enhancing NPP content to 0.40% or supplementing microbial phytase to 0.30 and 0.35% NPP diet. The nitrogen retention was significantly higher in 0.40% NPP diet compared with lower levels (0.30 or 0.35% NPP). Supplementation of microbial phytase to low NPP diet (0.30 and 0.35%) significantly increased nitrogen retention. The excretion of nitrogen decreased significantly in phytase-supplemented group compared with that of either 0.40 or 0.45% NPP diet. It is concluded that microbial phytase supplementation (500FTU/kg diet) to low NPP (0.30%) maize-soybean meal based poultry diets enhanced performance, increased retention nutrients (N, Ca and P) and improved bone mineralisation.